Analysis of Surgical Volume in Military Medical Treatment Facilities and Clinical Combat Readiness of US Military Surgeons - Dalton, Michael K; Remick, Kyle N; Mathias, Michael; Trinh, Quoc-Dien; Cooper, Zara; Elster, Eric A; Weissman, Joel S (JAMA surgery, 2022)
Low surgical volume in the US Military Health System (MHS) has been identified as a challenge to military surgeon readiness. The Uniformed Services University of Health Sciences, in partnership with the American College of Surgeons, developed the Knowledge, Skills, and Abilities (KSA) Clinical Readiness Program that includes a tool for quantifying the clinical readiness value of surgeon workload, known as the KSA metric. To describe changes in US military general surgeon procedural volume and readiness using the KSA metric. This cohort study analyzed general surgery workload performed across the MHS, including military and civilian facilities, between fiscal year 2015 and 2019 and the calculated KSA metric value. The surgeon-level readiness among military general surgeons was calculated based on the KSA metric readiness threshold. Data were obtained from TRICARE, the US Department of Defense health insurance product. The main outcomes were general surgery procedural volumes and the KSA metric point value of those procedures across the MHS as well as the number of military general surgeons meeting the KSA metric readiness threshold. Aggregate facility and regional market-level claims data were used to calculate the procedural volumes and KSA metric readiness value of those procedures. Annual adjusted KSA metric points earned were used to determine the number of individual US military general surgeons meeting the readiness threshold. The number of general surgery procedures generating KSAs in military hospitals decreased 25.6%, from 128 377 in 2015 to 95 461 in 2019, with a 19.1% decrease in the number of general surgeon KSA points (from 7 155 563 to 5 790 001). From 2015 to 2019, there was a 3.2% increase in both the number of procedures (from 419 980 to 433 495) and KSA points (from 21 071 033 to 21 748 984) in civilian care settings. The proportion of military general surgeons meeting the KSA metric readiness threshold decreased from 16.7% (n = 97) in 2015 to 10.1% (n = 68) in 2019. This study noted that the number of KSA metric points and procedural volume in military hospitals has been decreasing since 2015, whereas both measures have increased in civilian facilities. The findings suggest that loss of surgical workload has resulted in further decreases in military surgeon readiness and may require substantial changes in patient care flow in the MHS to reverse the change.